Pengaruh Model Pembelajaran Argument Driven Inquiry (ADI) terhadap Kemampuan Argumentasi Peserta Didik pada Pembelajaran Biologi - Hayati, Zahratul; Fuadiyah, Sa’diatul (Lembaga Yasin AlSys, 2023)
The Indonesian nation has now entered the 21st century, which requires students not to be consumed by negative issues spreading in society. Based on this, learning in schools needs to equip and train students' argumentation abilities. The Arqument Driven Inquiry (ADI) learning model is thought to be able to improve students' argumentation abilities. The Arqument Driven Inquiry (ADI) learning model is a model that creates an active learning atmosphere by guiding students to solve a problem through investigation and finding solutions to these problems in groups. The purpose of this study was to reveal how the influence of the Arqument Driven Inquiry (ADI) learning model on students' argumentation abilities. The research method used is the method of literature study. The data used is secondary data obtained from relevant articles. From the results of the data recapitulation of several related articles, it can be seen that there is an effect of using the Arqument Driven Inquiry (ADI) model on students' argumentation abilities. So it can be concluded that the Arqument Driven Inquiry (ADI) model can improve students' argumentation skills in biology learning.